Graphene-Infused Hybrid Biobattery–Supercapacitor Powered by Wastewater for Sustainable Energy Innovation - Sambhu Sapkota; Matthew Hummel; Mahzuzah Zahan; Sushma P. Karanam; Jejal Bathi; Namita Shrestha; Zhengrong Gu; Venkataramana Gadhamshetty (Inorganics, 2024)
Human society annually produces nearly 100 billion gallons of wastewater, containing approximately 3600 GWh of energy. This study introduces a proof of concept utilizing graphene materials to extract and instantly store this energy. A hybrid device, mimicking a microbial fuel cell, acts as both a battery and supercapacitor. Wastewater serves as the electrolyte, with indigenous microorganisms on the graphene electrode acting as biocatalysts. The device features a capacitive electrode using a 3D nickel foam modified with a plasma-exfoliated graphene mixture. Compared to controls, the Gr/Ni configuration shows a 150-fold increase in power output (2.58 W/m2) and a 48-fold increase in current density (12 A/m2). The Gr/Ni/biofilm interface demonstrates outstanding charge storage capability (19,400 F/m2) as confirmed by electrochemical impedance spectroscopy. Microscopy, spectroscopy, and electrochemical tests were employed to elucidate the superior performance of Gr/Ni electrodes. Ultimately, the capacitive energy extracted from wastewater can power small electrical equipment in water infrastructure, addressing energy needs in remote regions without access to a typical power grid.